Indirect Political Budget Cycles: Evidence from Chilean Municipalities - Osorio-Flores, R (Elsevier B.V., 2018)
Political budget cycles have been studied at the national and local level, separately. However, when local governments depend on national resources, the central government may have incentives to manipulate intergovernmental transfers to favor politically aligned mayors, in order to use their help to mobilize voters in the next national election. This generates an indirect Political Budget Cycle (iPBC). This paper documents the presence of an iPBC in Chile. We show that, during municipal election years, the government increases the overall amount of transfers to municipalities (local governments), and that these additional resources are allocated to the politically aligned mayors. We also report that transfers to aligned mayors are higher when the local races are tighter, suggesting that the government prefers to deviate resources towards swing municipalities. Finally, we show that transfers are correlated with municipal spending during electoral years, and with both local and national political electoral outcomes. © 2018 Elsevier B.V.